Wound healing activity of the ethanolic extract of terminalia chebula retz. - G.P.CHOUDHARY (International Journal of Pharma and Bio Sciences, 2010)
The wound healing activity of ethanolic extract of fruit of Terminalia chebula evaluated on excision and incision model, in albino rats, in the form of an ointment with two concentrations (5% and 10% w/w ointment of bark extract in simple ointment base).Both concentrations of the ethanolic extract showed significant response in both the wound types tested when compared with the control group. Nitrofurazone ointment (0.2%w/w) used as standard.